Examining the role of waste-to-energy in a circular economy in Finland with meeting a zero-waste goal - Peart, Joel (2016)
As the concept for circular economy gains traction in the world and the EU pushes for the transition from a linear economy to a circular economy model, the role of waste-toenergy is crucial in a circular economy as it is the last chance to extract value out of material at the same time as providing an alternative energy source, henceforth bringing together a closed-loop system. A functioning circular economy will also have minimal waste generated which is sync with the idea of zero-waste. How all these aspects really work together is the focal point of this Master’s thesis where the aim is to see how the three factors of waste-to-energy, the circular economy and a zero-waste goal work together in accomplishing their respective objectives and to access their performance and potential in Finland using other Nordic countries as benchmarks. A qualitative research method of four semi-structured interviews with experts in Finland involved in various circular economy was supported by secondary sourced data on the other Nordic countries and if found that WtE has additional benefits to Nordics compared to other countries due to district heating utilization of excess steam that provides heat during the long winter months so henceforth offers higher energy efficiency. The state of the circular economy in Finland was harder to ascertain with the difficulty in showing concrete examples of a CE due to misunderstanding of the relatively new theoretical term and the many related terms. The overall conclusion for Finland was that a zero-waste goal was not the correct aim to have as this could still mean high incineration, instead Finland should look at the exemplarily example of Denmark which aims to be incineration free in the future. There would still be a role for WtE, only to a less extent, dealing with hazardous and residual waste. The role of recycling will grow in line with a true CE model which means that energy sourced from WtE will decline, As a result Finland should plan accordingly and invest less in WtE infrastructure and more in other alternative energy sources.